The haves and the have-nots a brief and idiosyncratic history of global inequality - Milanovic, Branko (Basic Books, 2011)
One of the world's leading experts on wealth, poverty, and the gap that separates them, explains how wealth is unevenly spread throughout our world, now and through time. Economist Branko Milanovic uses history, literature and stories straight out of today's newspapers, to discuss one of the major divisions in our social lives: between the haves and the have-nots. He reveals just how rich Elizabeth Bennet's suitor Mr. Darcy really was; how much Anna Karenina gained by falling in love; how wealthy ancient Romans compare to today's super-rich; where in Kenyan income distribution was Obama's grandfather; how we should think about Marxism in a modern world; and how location where one is born determines his wealth. He goes beyond mere entertainment to explain why inequality matters, how it damages our economic prospects, and how it can threaten the foundations of the social order that we take for granted.--From publisher description.